2012
DOI: 10.1007/s10554-012-0153-y
|View full text |Cite
|
Sign up to set email alerts
|

Low contrast- and low radiation dose protocol for cardiac CT of thin adults at 256-row CT: usefulness of low tube voltage scans and the hybrid iterative reconstruction algorithm

Abstract: To evaluate the effect on image quality of a low contrast and radiation dose protocol for cardiac computed tomography (CT) using a low tube voltage, the hybrid-iterative reconstruction algorithm, and a 256-row CT scanner. Before clinical study, we performed phantom experiments to evaluate the hybrid iterative reconstruction technique. We randomly assigned 68 patients undergoing cardiac CT to one of two protocols; 33 were scanned with our conventional 120 kVp protocol, the contrast material (370 mgI/kg body wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 42 publications
5
43
0
Order By: Relevance
“…Nakaura et al 25 found that with a 256-row scanner and 80 kVp plus IR, the CM dose could be decreased by 50% (to 185 mgI/kg; mean CM dose, 29.4 AE 6.1 mL) at CCTA and that contrast enhancement in the ascending aorta was sufficient. Komatsu et al, 26 who used a 64-row CT scanner, two 80-kVp protocols, and a mean CM dose of 10 AE 4 or 15 AE 7 mL, reported that the image quality was acceptable.…”
Section: Discussionmentioning
confidence: 99%
“…Nakaura et al 25 found that with a 256-row scanner and 80 kVp plus IR, the CM dose could be decreased by 50% (to 185 mgI/kg; mean CM dose, 29.4 AE 6.1 mL) at CCTA and that contrast enhancement in the ascending aorta was sufficient. Komatsu et al, 26 who used a 64-row CT scanner, two 80-kVp protocols, and a mean CM dose of 10 AE 4 or 15 AE 7 mL, reported that the image quality was acceptable.…”
Section: Discussionmentioning
confidence: 99%
“…The use of these algorithms can also lead to reduced tube current or tube voltage (if necessary, with somewhat increased tube current), both of which reduce radiation dose without increasing image noise (Fig 2). The combination of iterative reconstruction and a low-tube voltage scan allows a decrease in the dose of intravenous contrast medium with preservation of image quality (28). On the basis of data from a prospective multicenter study, investigators have suggested that the use of adaptive statistical iterative reconstruction can reasonably reduce tube current and lower radiation dose (44% reduction in median dose) compared with filtered backprojection (27,29).…”
Section: Iterative Reconstructionmentioning
confidence: 99%
“…High-resolution acquisitions are becoming more feasible as IR tempers the negative effects of photon starvation [49][50][51]. Contrast material dose reductions may also be possible without prohibitive degradation of image quality [22]. Novel IR algorithms are also emerging that should expand IR applications.…”
Section: Future Directionsmentioning
confidence: 99%